Deceleration - Revealed Preference in Society and Win-Win-Strategy for Sustainable Management. Concept and Exprimental Evidence - Edeltraud Günther; Marco Lehmann-Waffenschmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2005)
Until recently "deceleration" has been little recognized as a technical term, or as an idea. However, it seems to be getting more attention now. For example the German magazine STERN dedicated a cover story to deceleration, in the Anglo-American world the "Quiet Life Hypothesis" is gaining followers, the "Heidelberger Club für Wirtschaft und Kultur" dedicated its annual meeting in 1998 to deceleration, and the competition for the German Study Award of the Körber Foundation in 2002 had the motto "Speed – the accelerated world." In Italy you can even study "Slow Food" and along German motorways you find signs with the slogan "be relaxed - just discover." Without any doubt, time is a decisive factor for the productivity and competitive advantages of companies. But more speed by continual, or even accelerated, acceleration may well be counter-productive and lead to an "acceleration paradox" - for example by product life cycles that are too short and therefore increase the share of R&D-costs or by "Pyrrhus" victories, that lead to "the winner's curse" instead of a stable market position. This acceleration paradox may show up in consumption, too. Consuming requires time and therefore competitors not only fight for their share of the consumers' cost budget, but also for their share of the consumers' time budget. It is this time budget, that must be split up into productive, consumptive and in all other leisure activities, such as going for a walk or playing chess, that are neither productive nor consumptive in an economic sense. The wide range of consumption goods in narrow markets and the increase in consumed goods and services together with the already mentioned shorter life cycles, e.g. of computers, cell phones or electronic equipment, are perceived by the consumers more and more as acceleration and personal burden. Speed can threaten the "happiness" of the consumers and so acceleration may become an "acceleration trap" for business and society. The term "deceleration" seems to be adequate for describing the opposite of acceleration. But is there truly a preference for deceleration in the society, and can deceleration become a paradigm in business management? These questions give the impulse for the research presented here by asking four questions and providing first answers: What are the reasons for acceleration in business and society? What have been the consequences of acceleration so far? Can deceleration contribute to sustainable management? Is there a preference for deceleration in society, and how can it be measured?
Keywords: 330; Deceleration; Sustainable Management; Experimental Economics; Zeit; Betriebliche Terminplanung; Nachhaltige Entwicklung; Willingness to pay; Experiment; Theorie